2022
DOI: 10.3390/microorganisms10020307
|View full text |Cite
|
Sign up to set email alerts
|

Algae and Their Metabolites as Potential Bio-Pesticides

Abstract: An increasing human population necessitates more food production, yet current techniques in agriculture, such as chemical pesticide use, have negative impacts on the ecosystems and strong public opposition. Alternatives to synthetic pesticides should be safe for humans, the environment, and be sustainable. Extremely diverse ecological niches and millions of years of competition have shaped the genomes of algae to produce a myriad of substances that may serve humans in various biotechnological areas. Among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 212 publications
1
30
0
Order By: Relevance
“…The influence of laminarin in SA accumulation on plants is controversial. Some studies observed an increase of SA in plants when stimulated with that compound [ 47 , 225 ], but other studies observed the inhibition of SA accumulation. SA is derived from the phenylpropanoid pathway and some studies established a correlation between SA accumulation and the increase in phenylalanine ammonia-lyase (PAL), a defense enzyme [ 229 ] that is a precursor of SA [ 230 ].…”
Section: Seaweed Elicitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of laminarin in SA accumulation on plants is controversial. Some studies observed an increase of SA in plants when stimulated with that compound [ 47 , 225 ], but other studies observed the inhibition of SA accumulation. SA is derived from the phenylpropanoid pathway and some studies established a correlation between SA accumulation and the increase in phenylalanine ammonia-lyase (PAL), a defense enzyme [ 229 ] that is a precursor of SA [ 230 ].…”
Section: Seaweed Elicitorsmentioning
confidence: 99%
“…Their exploitation is already vast in some industries, encompassing the food, cosmeceutical, and agricultural industries [ 42 ], but the search for other bioactivities has also been growing. One of them is the antimicrobial activity from algae compounds against phytopathogens [ 41 , 46 ], which remains poorly described against bacterial phytopathogens when compared with the amount of data reported regarding antibacterial activity against human pathogens [ 47 ]. Several compounds’ families have exhibited antimicrobial activity against a wide range of phytopathogens, such as pigments (carotenoids), fatty acids, sterols, terpenes, polysaccharides, phenolic compounds, proteins, and peptides [ 44 , 45 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pandit et al [ 33 ] summarized existing and incoming strategies to control plant pathogens using biological approaches, for example, the use of microbial strains and natural compounds to provide a natural protection. Algae (micro and macro) possess antibacterial, antiviral, antifungal, nematicide, insecticidal and herbicidal properties and represent a vast reservoir of unknown properties [ 34 ]. Amoebas are even less known and represent a considerable reservoir of unknown properties.…”
Section: Discussionmentioning
confidence: 99%
“…161 More importantly, the eld-level evaluation of microalgae or their cellular extracts is critical for the widespread acceptance of their application as an agronomic practice in green agriculture. The insecticidal properties of several macro-and microalgae as well as cyanobacteria have been reported and recently reviewed by Asimakis et al 162 The crude ethanolic extracts of a cyanobacterium (Nostoc carneum), green algae (Parachlorella kessleri, Ulva intestinalis, and Cladophora glomerata), and stonewort (Chara vulgaris) showed insecticidal activity against cotton leafworm (Spodoptera littoralis) when treated against the 2nd and 4th instars in the in vitro assay. 163 The ethanolic crude extracts contained an array of saturated and unsaturated fatty acids (particularly polyunsaturated u-6 linoleic, palmitic, oleic, myristic, a-linolenic, and 7,10-hexadecadienoic acids), essential oils, and phytol and other terpene compounds, and their effects were inhibitory to larval duration, percent pupal formation, pupal duration and weight, moth emergence (%), fecundity and longevity of adults, hatching of eggs, sex ratios, and even larvalpupal-moth malformations.…”
Section: Microalgae and Cyanobacteria As Biocontrol Agents Of Pathoge...mentioning
confidence: 99%